2009
DOI: 10.4049/jimmunol.0802008
|View full text |Cite
|
Sign up to set email alerts
|

CD2 Distinguishes Two Subsets of Human Plasmacytoid Dendritic Cells with Distinct Phenotype and Functions

Abstract: high pDCs secrete higher levels of IL12p40, express higher levels of costimulatory molecule CD80, and are more efficient in triggering proliferation of naive allogeneic T cells. Thus, human blood pDCs are composed of subsets with specific phenotype and functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
163
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(180 citation statements)
references
References 78 publications
11
163
1
5
Order By: Relevance
“…Surface expression of CD2 divides human pDCs into two distinct subsets. Whereas both CD2 lo and CD2 hi pDCs produce type I IFN, the CD2 hi subset secretes more IL12p40, triggers more T-cell proliferation (26), and is relatively resistant to apoptosis on the basis of higher BCL2 expression (28). Here we show that CD2 hi pDCs contain a unique subpopulation that expresses CD5 and CD81.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Surface expression of CD2 divides human pDCs into two distinct subsets. Whereas both CD2 lo and CD2 hi pDCs produce type I IFN, the CD2 hi subset secretes more IL12p40, triggers more T-cell proliferation (26), and is relatively resistant to apoptosis on the basis of higher BCL2 expression (28). Here we show that CD2 hi pDCs contain a unique subpopulation that expresses CD5 and CD81.…”
mentioning
confidence: 71%
“…Whether the diverse functions of pDCs are mediated by the same cells responding to different environmental cues or by distinct preprogrammed subsets or lineages is not clear, although several reports suggest the existence of phenotypically distinct subpopulations of pDCs in mice (23)(24)(25) and humans (26)(27)(28)(29)(30). Surface expression of CD2 divides human pDCs into two distinct subsets.…”
mentioning
confidence: 99%
“…Recently, it has been reported that gzmB is present in other leukocyte populations, namely, CD4 þ T cells, 33 B cells, 31 neutrophils, 29 basophils, 28 mast cells, 27 macrophages, 26 dendritic cells 32,52 and CD34 þ stem cells. 29,53 Although the function of gzmB produced by these cells is unknown, it seems to be granule associated.…”
Section: Serpinb9 and Granzyme Bmentioning
confidence: 99%
“…Furthermore, pDCs can interact synergistically with myeloid DCs by enhancing their priming ability in a contact-dependent manner, resulting in increased levels of Ag-specific CTLs (3,10). Finally, activated pDCs abrogate cancer cell replication and induce tumor cell death (11).…”
mentioning
confidence: 99%